VIDEO PROFIL SEBAGAI MEDIA INFORMASI POTENSI DAN KEARIFAN LOKAL DESA TREBUNGAN KECAMATAN MANGARAN - Yuliana, Dyan; Jannah, Raudatul; Azizah, Nur; Maulana, Andrico Bagus (STKIP PGRI SITUBONDO, 2024)
A village profile is needed to find out information and a description of potential, culture and local wisdom as well as an accurate, comprehensive and integral level of village development as stated in Minister of Home Affairs Regulation Number 12 of 2007. Through STKIP PGRI Situbondo Community Service (PkM) activities for the 2024 fiscal year, joint lecturers with students trying to help Trebungan Village, located in Mangaran District, Situbondo Regency, East Java Province, in making a video profile of the village. Based on problem identification, the latest Trebungan Village profile contains several data and information as required in Minister of Home Affairs Regulation Number 12 of 2007, especially for data on natural resource potential. However, other data is still incomplete. Therefore, the aim of this PkM activity is to create a video profile of Trebungan Village which contains complete information about the village, its potential and culture (local wisdom) and presents a video profile of the village which can be accessed in an electronic version by the entire community. The method used is data collection, namely observation, surveys, interviews and documentation. Evaluation of this activity is carried out directly during the profile creation activity, so that output can be produced that meets the wishes of the target audience. The output of this PkM activity is a village profile video which has been uploaded on the Trebungan Village website and social media (YouTube, Facebook and Instagram).